Real time assessment of smart concrete inspection with piezoelectric sensors - Quah, Noel Tan Kai (2024)
Utilization of an Electromechanical impedance (EMI) technique with Piezoelectric (PZT) sensors has showed potential for Structural Health Monitoring (SHM). The changes in mechanical structure via flexural bending and cracking can be detected by monitoring the deviations in electrical impedance signals recorded with embedded PZT sensors. This paper has conducted a comprehensive study on the potential of an EMI technique with embedded PZT sensors with 3D Concrete Printing (3DCP) structures subjected to flexural bending test until plastic failure. The impact of different Piezoelectric housing methods and materials has been studied comprehensively through the monitoring of EMI signals. Experimental results indicate that material housing types and thickness affect the sensitivity of EMI readings but also performed as a reinforcement when a load is directly applied. The embedded PZT sensors with the EMI technique have shown strong potential to address the cost and lifecycle challenges posed by traditional construction methods as the insertion of PZT sensors seamlessly functions with 3DCP workflows. Further developmental work can be carried out to address the sensitivity of the sensor, performance as a reinforcement, and installation automation. The results proved that the coated sensors could detect fractures in 3DCP concrete with decreased sensitivity on thicker coating layers through the variance in materials and coating thickness in the paper.